Pedagogical technology of the use of physical and recreational tools in the conditions of acquisition by students of the elective course - Shilko T.A.; Konkova S.I.; Radaeva S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to reveal the effectiveness of the use of physical and recreational tools in the conditions of students acquisition of the elective course. Methods and structure of the study. The experiment was conducted on the basis of Tomsk State University with the participation of students of the basic and preparatory medical groups who chose the elective course «Ushu». The training methodology includes the study of basic techniques, mastering the tao complexes «18 Forms of Changquan» and «32 Forms of Changquan». Sociological methods were used in the study: questionnaires and testing of functional and psychological tests for monitoring the functional state of students (coefficient of endurance, level of physical condition, Ruffier-Dixon test, etc.). Results and conclusions. This activity based on the developed pedagogical technology allowed students to get acquainted with a new type of physical activity, to increase the level of physical health. The results of the study confirm the effectiveness of this application in the system of physical education of students in the university as an elective discipline, contribute not only to the improvement of physical training, but also to the development of important personal qualities, the formation of a healthy lifestyle and the improvement of the general quality of life of student youth. The revealed main motive for choosing this occupation is interest in Chinese culture, desire to improve physical form, self-defense skills, desire for self-development and harmonization of personality.